Akcja Wyborcza Solidarność – brak marketingu politycznego i medialnego jako jedna z przyczyn upadku - Madera, Andrzej J. (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2004)
Although the Solidarity Election Action (AWS) had been the first impressive attempt to unite right-wing groupings after 1989 which was effected in practice, it failed to develop a united, coherent image for the purpose of contacts with the media throughout the whole period it was in power. Reality showed that right-wing politi- cians failed to take advantage of the assets of the new grouping. Incompetence of its leaders and absence of a coherent policy quickly overshadowed the success of the Soli- darity Election Action. As a consequence, Solidarity Election Action has wasted an enormous chance and failed to become a united group of the Polish right wing. Leaders of individual organizations composing the AWS did not give up their leaders’ ambitions, which became particularly significant towards the end of the AWS-UW (Solidarity Election Action – Liberty Union) coalition, when the right-wing block was eroding rapidly.
Solidarity Election Action (AWS) - Absence of Political and Media Marketing as One of Reasons for Failure